Hunting Wildlife and Wage Employment: Resource Use Strategies at Fort George, Quebec. - Feit, Harvey (My University, 1978)
Fort George, Quebec is an unusually large community in the Canadian north, and it provides itself with an unusually high subsistence production for its size. It is also a community with an unusually intense involvement in wage labor. We asked how a substantial level of subsistence production was being maintained, what strategies or models and plans guided hunters. Models developed in an earlier study at a Cree inland community, Waswanipi, were not sufficient to explain Fort George hunting success. Using hunters’ statements about their activities (ethno-models), several different strategies for harvesting resources by season and location were identified. The combination of migratory resources that seasonally pass through Fort George lands, including lands near this coastal settlement, provides access to particularly productive resources for specific periods of time. A key to the limiting conflict between intensive wage labor and subsistence production is the use of the migratory resources and other resources with high biological yields available near the settlement, and the adaptation of work schedules to seasonal migrations. Workers who used this strategy were able to achieve most of the subsistence food production taken by full-time hunters who could range more widely. Hunters with more time were more widely distributed at seasons when migratory game were not available.
I want to thank the Chisasibi people of Fort George for their support and for helping me to understand something about how they hunted and used and stewarded their lands. Most of the quantitative records that I used in this research were the result of earlier collaborations of Chisasibi people: with the Native Harvesting Research team (NHR); with research done for the Grand Council of the Crees (GCC) including the Fort George Land Use and Subsistence Economy Study led by Martin Weinstein, and the Fort George Land Use and Occupancy Study led by Alan Penn; and research by Fikret Berkes. I was also assisted by Richard Salisbury who commented on the report.
Keywords: Hunting Strategies; Migratory Resources; Sedentarized Hunting; Jobs and Hunting; Ethno-ecology; Indigenous Knowledge; Subsistence; Fort George; Chisasibi people; James Bay Cree